Indirect Enhancement of ALD Thin-Film Properties Induced by the ECAP Modification of an As-Extruded Mg-Ca Alloy - Pi-Chen Lin; Jun-Yu Li; Hou-Jen Chen; Kaifan Lin; Miin-Jang Chen; Kun-Ming Lin; Hsin-Chih Lin (Micromachines, 2024)
The purpose of this study is to investigate the indirect effects on the properties of ZrO2 films deposited by atomic layer deposition (ALD) when an Mg-Ca alloy is modified through equal-channel angular pressing (ECAP) following extrusion. The study aims to understand how the increase in CaO content in the native oxide layer of the Mg-Ca alloy influences the crystallinity and defect density of the ZrO2 film. Consequently, the corrosion protection performance of the ZrO2 film is enhanced by 1.2 to 1.5 times. A reduction in the anti-scratch property of the ZrO2 film was also observed, with a critical load reduction of 34 μN. This research provides a detailed analysis of the modifications induced by ECAP on the as-extruded Mg-Ca alloy and its subsequent impact on the properties of the ZrO2 film.